Making Fisheries Management Work Implementation of Policies for Sustainable Fishing - Gezelius, Stig S.; Raakjær, Jesper (Reviews: Methods and Technologies in Fish Biology and Fisheries ;, 2008)
The state of the Northeast Atlantic fisheries in recent years has highlighted implementation as the Achilles heel of modern fisheries management: discards, unreported or misreported landings are in many cases recognised to effectively subvert sound conservation goals. Implementation is thus a key factor in avoiding fisheries crises. While social science literature on fisheries management has tended to regard the implementation of resource conservation policies as a question of effective enforcement, this book seeks to widen the perspective taken on implementation in fisheries management. The cases presented in this volume addresses legal, administrative, and political challenges regarding implementation of resource conservation policies. The book addresses problems relating to goal achievement, but also causes of deliberate change of political goals during implementation. Fisheries management systems are embedded in inert social structures and natural conditions that vary among different states. Consequently, the book takes a historical and comparative approach, describing the historical developments of national implementation systems and the conditions that shaped their development. It thus seeks to explain why national fisheries management systems have evolved differently, focusing on Norwegian, Faeroese, and EU/Danish management systems. The descriptive and explanatory outlines are accompanied by qualitative assessments of the systems effectiveness as tools for collective action.